2017
DOI: 10.1038/s41598-017-05146-x
|View full text |Cite
|
Sign up to set email alerts
|

Herbal formula YYJD inhibits tumor growth by inducing cell cycle arrest and senescence in lung cancer

Abstract: Lung cancer represents a major cause of cancer-related death worldwide. Although various tactics and anti-tumor drugs have been used to improve curative effects, five-year survival rate of lung cancer patients remains poor. In this study, we investigated the action and underlying mechanisms of our recently optimized Chinese herbal formula Yangyinjiedu (YYJD) against lung cancer. YYJD significantly inhibits the proliferation of lung cancer cell lines (95-D, A549, H460 and H1975) by inducing cell cycle arrest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Cell cycle progression plays an important role in tumour growth, and its regulation is an effective strategy to control tumour growth. It has been reported that the active ingredients of traditional Chinese medicine can arrest tumour cells at different cell cycle, which in turn inhibit tumour cell growth, proliferation, and induce apoptosis [16] [17]. In present study, Acetylshikonin blocked cell cycle progression at G0/G1 phase, which demonstrated that Acetylshikonin interfered with the normal tumour cell cycle and inhibited tumour growth.…”
Section: Acetylshikonin Inhibited the Growth Of Xenografted Tumours Isupporting
confidence: 57%
“…Cell cycle progression plays an important role in tumour growth, and its regulation is an effective strategy to control tumour growth. It has been reported that the active ingredients of traditional Chinese medicine can arrest tumour cells at different cell cycle, which in turn inhibit tumour cell growth, proliferation, and induce apoptosis [16] [17]. In present study, Acetylshikonin blocked cell cycle progression at G0/G1 phase, which demonstrated that Acetylshikonin interfered with the normal tumour cell cycle and inhibited tumour growth.…”
Section: Acetylshikonin Inhibited the Growth Of Xenografted Tumours Isupporting
confidence: 57%
“…Our previous studies indicated that it induces cellular apoptosis through activation of FAS and DR4, and exerts synergistic effects in combination with chemotherapy on lung cancer cell apoptosis . Using computational algorithms, recently we optimized the ingredients of JFK formula and the optimized formula Yangyinjiedu (YYJD) exhibits anti‐tumour effect by inducing lung cancer cell senescence . In this study, we further examined the anti‐tumour mechanism of YYJD and demonstrated that YYJD induces apoptosis by activating transcriptional regulator EGR1 in lung cancer cells.…”
Section: Introductionmentioning
confidence: 94%
“…For in vitro experiments, a quantified amount (50 mL) of the GJXLT extract was processed with a freeze dryer to obtain crystal powder. Freeze-dried powder was dissolved in culture medium and filtered and stored as a stock solution (142 mg/mL) at -20°C [ 11 ].…”
Section: Methodsmentioning
confidence: 99%